(untitled) (Architecture Image Studies, 2025)
This study aims to identify major research trends and structural connections within multicultural and arts education in Korea through a text-mining and topic-modeling approach. A total of 150 academic papers published between 2008 and 2024 were analyzed to explore how themes of intercultural competence and socially engaged art have evolved over time. Using latent Dirichlet allocation (LDA) and coherence-based validation, eight dominant topics were extracted: multicultural sensitivity, intercultural communication, arts-based integration, community engagement, policy development, identity expression, digital arts, and inclusive learning environments. Temporal and network analyses revealed a paradigm shift from cultural adaptation to intercultural understanding, and subsequently to participatory and solidarity-based discourses. The results show that Korean multicultural and arts education research has evolved from teacher-centered approaches toward learner- and community-oriented perspectives. The growing focus on socially engaged and digital arts education reflects the expanding intersection between cultural participation and civic inclusion. Moreover, the integration of interculturalism and participatory art suggests a move toward a holistic model of cultural-arts education bridging theory, policy, and practice. These findings demonstrate that multicultural and arts education in Korea has progressed from “understanding” to “participation,” and finally toward “solidarity,” indicating an emerging framework of Intercultural Arts Education. This study provides empirical evidence linking interculturalism and participatory art within educational practice and offers foundational insights for developing inclusive and community-oriented frameworks for cultural and arts education.